2012
DOI: 10.1002/ijc.27563
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a simple rapid human papillomavirus DNA test in rural Nigeria

Abstract: Success of the new HPV DNA test for low-resource settings (careHPV™ test, QIAGEN Gaithersburg, Inc.; Gaithersburg, MD) requires good test performance when operated by personnel with limited laboratory experience. We evaluated the transferability, reliability, and accuracy of the careHPV test nested within a cervical screening project in a large Nigerian village. CareHPV testing was performed on screen-positive (n=345) and screen-negative (n=42) women attending colposcopy (68.3% of referred). Biopsies of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 15 publications
(37 reference statements)
0
38
0
Order By: Relevance
“…Previous studies of careHPV TM have shown sensitivity and specificity that approach that of HC2, a U.S. Food and Drug Administration-approved test (Qiao et al, 2008;Zhao et al, 2010). Moreover, the workflow of careHPV TM is similar but simpler than the HC2 test with a lower cost and simpler administration, and can be run by secondary school graduates without laboratory experience, using a training of the trainer model (Gage et al, 2012). In Dec of 2013, the latest WHO guidelines recommended using HPV testing as the primary screening method for cervical cancer in areas with enough resources.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of careHPV TM have shown sensitivity and specificity that approach that of HC2, a U.S. Food and Drug Administration-approved test (Qiao et al, 2008;Zhao et al, 2010). Moreover, the workflow of careHPV TM is similar but simpler than the HC2 test with a lower cost and simpler administration, and can be run by secondary school graduates without laboratory experience, using a training of the trainer model (Gage et al, 2012). In Dec of 2013, the latest WHO guidelines recommended using HPV testing as the primary screening method for cervical cancer in areas with enough resources.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of careHPV have shown sensitivity and specificity that approach that of Hybrid Capture 2 (HC2; QIA-GEN; ref. 11), a U.S. Food and Drug Administrationapproved test, and can be run by secondary school graduates without laboratory experience, using a training of the trainer model (12).…”
Section: Introductionmentioning
confidence: 99%
“…Specialized training and education are not required to run the test. It has been evaluated in multiple countries and found that careHPV is a sensitive and reasonably specific screening test for cervical precancer and cancer (7)(8)(9)(10)(11)(12). In 2012, the China Food and Drug Administration approved this test for cervical cancer screening (13).…”
mentioning
confidence: 99%